The impact of social isolation on HPA axis function, anxiety-like behaviors, and ethanol drinking - Butler, Tracy R.; Ariwodola, Olusegun; Weiner, Jeffrey (Frontiers in Integrative Neuroscience, 2014)
Dysregulation of the hypothalamic-pituitary-adrenal (HPA) axis is often observed in alcoholics and humans subjected to early life stress, and animal models of ethanol (EtOH) dependence. We examined HPA axis function in a rodent model of early life stress that engenders increases in behavioral and neurobiological risk factors of alcoholism. Long-Evans male rats were group housed (GH) or socially isolated (SI) for six weeks during adolescence. We examined the corticosterone (CORT) response to stress with and without dexamethasone (DEX) and anxiety-like behaviors. Following the DEX suppression test and behavioral assays, half of the cohort engaged in six weeks of EtOH drinking in a homecage, two-bottle choice intermittent access model. A subset of the cohort was not exposed to EtOH, but was used for electrophysiological measurement of glutamatergic synaptic plasticity in the basolateral amygdala (BLA). Correlational analyses examined relationships between measures of CORT, anxiety-like behaviors, and EtOH intake/preference. With DEX pre-treatment, SI rats failed to suppress CORT in response to an acute stress; GH rats showed a significant suppression. In SI rats, there was a significant negative correlation between baseline CORT and EPM open arm time, as well as significant positive correlations between baseline CORT and both EtOH intake and preference. No significant relationships between baseline CORT and behavioral measures were observed in GH rats. Glutamatergic plasticity in the BLA was similar in magnitude between GH and SI rats, and was not altered by exogenous application of CORT. These data suggest that HPA axis function is affected by SI, and this is related to antecedent anxiety-like behavior and may predispose for future EtOH self-administration. Relationships between HPA axis function, anxiety, and EtOH measures in SI rats further strengthens the utility of this paradigm in modeling vulnerability for affective disorders and alcoholism.